You are on page 1of 3

EE113: Digital Signal Processing Fall 2011

Prof. Abeer Alwan October 13, 2011


TA: Jianshu Chen and Sen Li
Solution to Quiz 1
1. Solution:
(a) From sampling theory, we have x(n) = x(t)|
t=nTs
, where T
s
is the sampling interval. We
know that sampling rate is 180 samples/sec, so T
s
= 1/180 sec. Thus, we get
x(n) = cos(120t) + sin(60t) + 10|
t=n/180
= cos(
2
3
n) + sin(

3
n) + 10
(b) Let x
1
(n) = cos(
2
3
n) and x
2
(n) = sin(

3
n), therefore, x(n) = x
1
(n) + x
2
(n) + 10.

1
=
2
3

1
N
1
= 2k = N
1
= 3k = N
1
= 3

2
=

3

2
N
2
= 2k = N
2
= 6k = N
2
= 6
the period N should be the least common multiple of N
1
and N
2
, which is 6.
2. Solution:
(a) The system is linear. Assume x
1
(n) is an arbitrary input with corresponding output
y
1
(n), and x
2
(n) is another arbitrary input with output y
2
(n). Then, y
1
(n) and y
2
(n)
can be written as
y
1
(n) = sin
_

4
n
_
x
1
(n 1) + x
1
(n)
y
2
(n) = sin
_

4
n
_
x
2
(n 1) + x
2
(n)
Then, the output corresponding to input x(n) = ax
1
(n) + bx
2
(n) is
y(n) = sin
_

4
n
_
[ax
1
(n 1) + bx
2
(n 1)] + [ax
1
(n) + bx
2
(n)]
= a
_
sin
_

4
n
_
x
1
(n 1) + x
1
(n)
_
+ b
_
sin
_

4
n
_
x
2
(n 1) + x
2
(n)
_
= ay
1
(n) + by
2
(n)
(b) The system is causal, because the output y(n) at time n is only determined by the
current and previous inputs: {x(n), x(n 1)}.
(c) The system is not time-invariant. Let us denote y
0
(n) as the response to input x
0
(n).
Then, we have
y
0
(n) = sin
_

4
n
_
x
0
(n 1) + x
0
(n)
EE113 - Fall 2011 1 of 3
Then, the response to x(n) = x
0
(n n
0
) can be written as
y(n) = sin
_

4
n
_
x(n 1) + x(n)
= sin
_

4
n
_
x
0
(n n
0
1) + x
0
(n n
0
)
= y
0
(n n
0
) = sin
_

4
(n n
0
)
_
x
0
(n n
0
1) + x
0
(n n
0
)
(d) The system is BIBO stable. Assume x(n) is an arbitrary bounded input, i.e.,
|x(n)| B
x
, n
Then, the corresponding output satises
|y(n)| =

sin
_

4
n
_
x(n 1) + x(n)

sin
_

4
n
_
x(n 1)

+|x(n)|

sin
_

4
n
_

|x(n 1)| +|x(n)|


1 B
x
+ B
x
2B
x
3. Solution:
(a) According to the gure, we can write the system dierence equation as
y(n) = 3y(n 1) + x(n) + 2x(n 1)
(b) With initial condition y(1) = 0 and x(n) = (n), we need to solve the impulse response
from the following dierence equation:
h(n) = 3h(n 1) + (n) + 2(n 1), h(1) = y(1) = 0
from which we can write:
h(0) = 3h(1) + (0) + 2(1) = 1
h(1) = 3h(0) + (1) + 2(0) = 3 + 2 = 1
h(2) = 3h(1) + (2) + 2(1) = 3 (1)
h(3) = 3h(2) + (3) + 2(2) = (3)
2
(1)
.
.
.
h(n) = (3)
n1
, n 1
In summary, the closed form expression for h(n) should be
h(n) = (n) +
1
3
(3)
n
u(n 1)
EE113 - Fall 2011 2 of 3
(c) Given that the input x(n) = u(n), the output of the system is
y(n) = h(n) u(n)
=
_
(n) +
1
3
(3)
n
u(n 1)
_
u(n)
= (n) u(n) +
1
3
(3)
n
u(n 1) u(n)
= u(n) +
1
3
n

k=1
(3)
k
u(n 1)
= u(n) +
1
3
(3) (3)
n+1
1 (3)
u(n 1)
= u(n)
1
12
_
3 + (3)
n+1

u(n 1)
EE113 - Fall 2011 3 of 3